INVESTMENT SENSITIVITY AND SERVICE LEVY TARIFF SCHEME: CASE STUDY OF EAST SURABAYA HOSPITAL - Astasari, Arianti Widi; Oetomo, Wateno; Sajiyo, Sajiyo (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2024)
As one of the largest cities in Indonesia, the City of Surabaya has an obligation to provide excellent health services for its residents. Consequently, the Surabaya City Government is required to provide a general hospital that can receive referrals from the government-owned Community Health Centers. To fulfill this obligation, the Surabaya City Government built the East Surabaya Hospital, located in the Rungkut Sub-District. East Surabaya Hospital is a strategic project that necessitates an investment feasibility analysis. This analysis was conducted using the Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), and Benefit-Cost Ratio (BCR) parameters. Following the feasibility analysis, a sensitivity analysis was performed to examine changes in management costs and the health service levy rates for each tariff alternative. Based on the investment feasibility analysis of four tariff alternatives, two alternatives—alternative 1 and alternative 3—were deemed worthy investments. In contrast, alternatives 2 and 4 were found to be unfeasible, as the NPV parameter showed negative values and the IRR value was lower than the Minimum Acceptable Rate of Return (MARR). However, the sensitivity analysis indicated that alternatives 2 and 4 could become feasible if alternative 2’s management cost is reduced by 14.4% and alternative 4’s management cost is reduced by 2.8%. Conversely, alternative 1 might become unfeasible if the management cost increases by 7%, and alternative 3 might become unfeasible if the management cost increases by 3.1%.